STUDI TENTANG PERSEPSI MASYARAKAT TERHADAP BAJU KURUANG BASIBA DI NAGARI MUARO PANEH KABUPATEN SOLOK PROVINSI SUMATERA BARAT - Wita Afrianti; Hambali Hambali; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack : This study aims to determine how people's perceptions of Kuruang Basiba clothes in Nagari Muaro Paneh, Solok Regency, West Sumatra Province. This research use desciptive qualitative approach. The informants who were examined using a purposive sampling technique were the head of the bundo Kanduang Nagari Muaro Paneh and some of its members, Niniak Mamak, and the Nagari Muaro Paneh community. Data collection techniques used were observation, questionnaire, interview and documentation. With primary and secondary data sources. Based on the results of the research carried out, it can be concluded that people's perceptions of the Kuruang Basiba clothing began to develop in a better direction because the Kuruang Basiba clothes are the typical clothes of the area that became the identity of women in Minangkabau. Niniak Mamak along with Bundo Kanduang began to promote Nagari's regulations regarding dress codes, especially at traditional events.Key Words : Kuruang Basiba Clothes